Proceedings of INTCESS 2021- 8th International Conference on Education and Education of Social Sciences 2021
DOI: 10.51508/intcess.2021163
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Impact of Supervisor Support on Knowledge Seeking Intention of International Students: A Conceptual Framework

Abstract: The paper integrates the theory of planned behavior concepts, attitude, subjective norms, self-efficacy directly related to knowledge-seeking intention, and it further proposes the moderating role of the supportive supervisor in the relationship with attitude, subjective norms, self-efficacy directly related to the knowledgeseeking intention of international students within Chinese academic settings. The higher educational institution globally trying to attract the educational aspirants and offer a quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In this study's context, KSI refers to the extent to which students willingly engage in activities that could help them acquire knowledge (Agolla et al, 2019;Chia-An Tsai & Kang, 2019;Khuram, Wang, et al, 2021b;Veeravalli et al, 2019).…”
Section: Knowledge Seeking Intention (Ksi)mentioning
confidence: 99%
“…In this study's context, KSI refers to the extent to which students willingly engage in activities that could help them acquire knowledge (Agolla et al, 2019;Chia-An Tsai & Kang, 2019;Khuram, Wang, et al, 2021b;Veeravalli et al, 2019).…”
Section: Knowledge Seeking Intention (Ksi)mentioning
confidence: 99%
“…Prior studies have found that a supportive supervisor significantly influences an individual's commitment that enables them to perform high and achieve goals (Khuram et al, 2021b;Yang et al, 2020), ultimately leading to productivity in doctoral research. Therefore, this study aims to examine the relationship between SS and research productivity.…”
Section: Introductionmentioning
confidence: 99%